Numerical study on heat loss from the surface of solar collector tube filled by oil-NE-PCM/Al2O3 in the presence of the magnetic field - Abu-Hamdeh, Nidal H.; Abusorrah, Abdullah M.; Bayoumi, Mohannad M.; Öztop, Hakan Fehmi; Sun, Chuan (Springer, 2021)
The natural convection of the oil-NE-PCM/Al2O3 inside the parabolic trough collector is studied. To simulate nanoencapsulate-phase change material (NE-PCM), the core PCM is made of n-nonadecane encapsulated in a shell of polyurethane. Density and specific heat capacity of NE-PCM are adopted from this ratio. PCMs are known for their thermal storage capability. Nanoparticles dissipation is simulated using Buongiorno's two-phase model. Solar radiation and heat loss are taken into account. Furthermore, porous media and magnetic field are added to enhance the heat transfer. The effects of incidence angle, Rayleigh number, Hartman number, and nanofluid volume fraction on the heat loss, efficiency, Nusselt number, streamlines, and isothermal lines are investigated. The heat loss is reduced by increasing Rayleigh number, Hartman number, and the incidence angle. A decrement is seen in the maximum temperature of the surface of the tube by augmenting Rayleigh number and incidence angle. The heat transfer rate is increasing with the increment of Rayleigh number, Hartman number, and incidence angle. It is observed that the heat transfer rate augments up to 30% by increasing Hartman number.
Keywords: PCM; Buongiorno’ s mathematical model; MHD; Solar radiation; PTC